SECURE SMART HOME DESIGN AND ANALYSIS FOR ELDERLY PEOPLE USING INTERNET OF THINGS (IOT) TECHNOLOGIES - Dr.D.Devi Aruna (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The Internet of Things technology is used for increase the old people living securely in environment of smart home and assist their caregivers. The smart homes are developed with automation of appliances and activities monitoring. The goal of smart home is to assure home resident safe. To increase the elder safety by using the IoT sensor and detect the attackers. The anomaly detection system is the system which identifies the interruption of network and computer by observing the behaviour of the system. This research paper analyzes and detects the behaviour of abnormal. This report discusses the system of anomaly detection based smart home from the perspective of security. The secure model of smart home is developed using Cisco packet tracer and device of IoT network is simulated and analysed the result.